Рhysics and design of wide-aperture bipolar particle sources - Dudin, S.V. (Вопросы атомной науки и техники, 2013)
A review of known designs of bipolar particle sources is presented classifying them by spatial or temporal separation of the oppositely charged particles. Both ion-electron and ion-ion sources are considered. Possibilities of creating bipolar ion-ion source are discussed basing on recent research results from Ecole Polytechnique (France) and from V.N. Karazin Kharkоv National University (Ukraine), particularly on comparative study of the sources with magnetic and electrostatic electron filters. Обзор известных конструкций биполярных источников заряженных частиц проведен с классификацией их по пространственной или временной сепарации противоположно заряженных частиц. Рассмотрены как ион-электронные, так и ион-ионные источники. Возможности создания биполярных ион-ионных источников обсуждаются на основе результатов последних исследований в Ecole Polytechnique (Франция) и в Харьковском национальном университете имени В.Н. Каразина (Украина), в частности, сравнительного изучения магнитных и электростатических электронных фильтров. Огляд відомих конструкцій біполярних джерел заряджених частинок проведено з класифікацією їх по просторовій або часовій сепарації протилежно заряджених частинок. Розглянуто як іон-електронні, так і іон- іонні джерела. Можливості створення біполярних іон-іонних джерел обговорюються на основі результатів останніх досліджень в Ecole Polytechnique (Франція) та в Харківському національному університеті імені В.Н. Каразіна (Україна), зокрема, порівняльного вивчення магнітних і електростатичних електронних фільтрів.